Access and gaps in maternal–child health services among housewives living with HIV in Yogyakarta, Indonesia: an in-depth interview study - Fitriana Putri Utami; Rochana Ruliyandari; Suci Puspita Ratih; Nik Daliana Binti Nik Farid (Universitas Gadjah Mada, 2026)
Purpose: This study examines access to antiretroviral therapy (ART), reproductive health services, and peer support among housewives living with HIV. It identifies barriers and unmet needs in maternal and child HIV care. Methods: This qualitative case study has five housewives living with HIV purposively selected as primary informants, supported by three HIV service providers as triangulation. Data were collected through in-depth interviews and analyzed using a thematic analysis. Results: Adult anti- retroviral therapy (ART) services were generally accessible at public health centers; however, participants often avoided facilities near their homes to prevent unintended disclosure and stigma. Maternal health services, including Prevention of Mother-to-Child Transmission (PMTCT), were avail- able but unevenly implemented, with comprehensive care concentrated in referral hospitals and variable provider familiarity with PMTCT protocols. Limited contraceptive use reflects misconceptions about reproductive health needs among married women with HIV. Peer support groups were crucial for psychosocial support and sustained engagement in care. Major gaps were identified in child health services, particularly pediatric HIV care, marked by hospital-centered ART provision and culturally appropriate guidance for HIV status disclosure to perinatally infected children. Conclusion: Although some maternal–child health services are accessible, substantial gaps remain in PMTCT, reproductive health, and pediatric HIV care. Strengthening provider capacity, addressing stigma, and developing integrated, child-friendly services—including clear guidance on pediatric HIV disclosure—are needed to support housewives living with HIV and their families.